2018
DOI: 10.5194/bg-2018-55
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimethylsulfide (DMS) production in polar oceans may be resilient to ocean acidification

Abstract: Abstract. Emissions of dimethylsulfide (DMS) from the polar oceans play a key role in10 atmospheric processes and climate. Therefore, it is important we increase our understanding of how DMS production in these regions may respond to environmental change. The polar oceans are particularly vulnerable to ocean acidification (OA). However, our understanding of the polar DMS response is limited to two studies conducted in Arctic waters, where in both cases DMS concentrations decreased with increasing acidity. Here… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…An experimental assessment of the impact of ocean acidification on DMS-producing planktonic communities of Baffin Bay during NETCARE (Hussherr et al, 2017) revealed that DMS production may decrease by 25 % under end-of-the-century scenario reductions of pH ( pH T = −0.48), confirming results observed in another Arctic study in the Svalbard archipelago which showed a 35 % decrease in DMS production (Archer et al, 2013). Other studies, however, have suggested that organisms thriving in Arctic waters may already be resilient to moderate or J. P. D. Abbatt et al: Overview paper: New insights into aerosol and climate in the Arctic acute natural fluctuations in pH, exhibiting a high capacity to compensate for modifications in pH (Hoppe et al, 2018) and no significant changes in DMS following acidification (Hopkins et al, 2018). Further experimentation is needed to identify the underlying causes for these contrasting DMS responses to ocean acidification in Arctic waters.…”
Section: Marine and Coastal Biogenic Aerosol Precursorssupporting
confidence: 78%
“…An experimental assessment of the impact of ocean acidification on DMS-producing planktonic communities of Baffin Bay during NETCARE (Hussherr et al, 2017) revealed that DMS production may decrease by 25 % under end-of-the-century scenario reductions of pH ( pH T = −0.48), confirming results observed in another Arctic study in the Svalbard archipelago which showed a 35 % decrease in DMS production (Archer et al, 2013). Other studies, however, have suggested that organisms thriving in Arctic waters may already be resilient to moderate or J. P. D. Abbatt et al: Overview paper: New insights into aerosol and climate in the Arctic acute natural fluctuations in pH, exhibiting a high capacity to compensate for modifications in pH (Hoppe et al, 2018) and no significant changes in DMS following acidification (Hopkins et al, 2018). Further experimentation is needed to identify the underlying causes for these contrasting DMS responses to ocean acidification in Arctic waters.…”
Section: Marine and Coastal Biogenic Aerosol Precursorssupporting
confidence: 78%
“…However, other factors affecting regional ocean biogeochemistry will also be important, such as natural variability in carbonate chemistry and the buffering capacity of the ocean surface (Hopkins et al, 2018).…”
Section: The Claw Hypothesismentioning
confidence: 99%
“…acute natural fluctuations in pH, exhibiting a high capacity to compensate for modifications in pH (Hoppe et al, 2018) and no significant changes in DMS following acidification (Hopkins et al, 2018). Further experimentation is needed to identify the underlying causes for these contrasting DMS responses to ocean acidification in Arctic waters.…”
Section: Marine and Coastal Biogenic Aerosol Precursorsmentioning
confidence: 99%